Conflict of interest in nutrition: Where’s the power? Comment on “Towards preventing and managing conflict of interest in nutrition policy? An analysis of submissions to a consultation on a draft WHO tool” - Harris, Jody; Nisbett, Nicholas; Gillespie, Stuart (Kerman University of Medical Sciences, 2022)
Actual or perceived conflict of interests (COIs) among public and private actors in the field of nutrition must be managed. Ralston et al expose sharply contrasting views on the new World Health Organization (WHO) COI management tool, highlighting the contested nature of global debates. Both the WHO COI tool and the Ralston et al paper are largely quiet on aspects of power among different actors, however, which we argue is integral to these conflicts. We suggest that power needs to be acknowledged as a factor in COI; that it needs to be systematically assessed in COI tools using approaches we outline here; and that it needs to be explicitly addressed through COI mechanisms. We would recommend that all actors in the nutrition space (not only private companies) are held to the same COI standards, and we would welcome further studies such as Ralston et al to further build accountability.